Identifying sputum specimens of high priority for examination by enhanced mycobacterial detection, identification, and susceptibility systems (EMDISS) to promote the rapid diagnosis of infectious pulmonary tuberculosis. Issue 8 (1st August 2001) - Freeman, R; Magee, J; Barrett, A
Abstract : Aims —To compare clinical information and sputum microscopy as methods for the selection of samples for enhanced mycobacterial detection, identification, and susceptibility systems (EMDISS) to promote the rapid diagnosis of patients with infectious pulmonary tuberculosis. Methods —Two thousand, two hundred and sixty four specimen request forms were examined for clinical details, which were then used to identify specimens likely to yield Mycobacterium tuberculosis on culture. These results were compared with the results of sputum microscopy for acid fast bacilli (AFB). Both methods were assessed against the results of culture using a combination of continuous automated mycobacterial liquid culture (CAMLiC) and conventional solid culture. Results —Classification based on clinical details was an inefficient method of identifying high priority specimens for EMDISS. Although, when given, clinical details were often consistent, a substantial proportion of specimens arrived with no details. This approach would result in the referral of at least 16% of the workload but lead to the detection by culture of only 46% of the M tuberculosis present within it. In contrast, microscopy for AFB defined a much smaller number of specimens (4.8% of the total), which contained 90% of the M tuberculosis isolates. Conclusions —Microscopy for AFB is the most efficient method for defining sputum specimens suitable for referral for enhanced mycobacteriological techniques. However, it is essential that the methods used for smear preparation and microscopy are of the highest possible standard, otherwise some patients with infectious pulmonary tuberculosis will be denied, unnecessarily, the benefits of important advances in mycobacteriology.